Indian and Western philosophical concepts in religion - Jain, Pankaj; Long, Jeffery D. (Explorations in Indic traditions: theological, ethical, and philosophical, 2023)
"This volume is based on innovative ideas coming from different Indic philosophies and how they can enrich the theory and methods in religious studies"--